(untitled) (International Journal of Medical and Surgical Sciences, 2020)
The outbreak of the coronavirus effects on people’s daily lives. Like nothing most people have experienced before. One of the many affected sectors is education In response to Covid-19 pandemic, medical education faculty have quickly transitioned the curriculum to online formats. But no matter the quality of the online resource, do not provide the same level of understanding of complex anatomical relationships as studying human bodies. Under restriction of social isolation because of Covid-19 pandemic, human anatomical dissection takes a compulsory break. Afterward students will come back to their essential training in dissection room.